The Impact of Packaging Elements on Consumer Buying Behavior in Food Industry - Shafig AL-HADDAD; Hala ABURADAHA; Esraa KHATER (Communications of International Proceedings, 2020)
This research aims to study the factors that affect “consumer buying behaviour” in the food industry in Jordan. The main objective is to know if there is any influence of different packaging elements on the behaviour of consumer buying method through investigating the influence of multiple independent variables on research’s dependent variables, this study has been considered in Amman-Jordan, a questionnaire has been used to collect data. Moreover, for analysis purposes, SPSS software was used. The study sample consisted of a hundred respondents and tested the following packaging elements: “packaging material, packaging colour, packaging printed information, design of wrapper in packages, font style and innovation”, it studied the extent of their influence on “consumer buying behaviour”. According to the findings, the material of packs and the design of wrapper have an obvious influence on “consumer buying behaviour” in the food industry, while the other elements do not influence “consumer buying behaviour”. Independent variables influence by a percentage of 45% on the dependent variable, this means other elements are influencing “consumer buying behaviour”.
Keywords: Packaging Elements; Buying Behavior; Food Industry.